2019
DOI: 10.1177/0969733019849464
|View full text |Cite
|
Sign up to set email alerts
|

Ethical sensitivity and perceptiveness in palliative home care through co-creation

Abstract: Background: In research on co-creation in nursing, a caring manner can be used to create opportunities whereby the patient’s quality of life can be increased in palliative home care. This can be described as an ethical cornerstone and the goal of palliative care. To promote quality of life, nurses must be sensitive to patients’ and their relatives’ needs in care encounters. Co-creation can be defined as the joint creation of vital goals for patients through the process of shared knowledge between nurses, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…This fundamental focus on alleviating (or avoiding unnecessary) suffering is on an ontological level, thus applicable to various models of nursing and nursing care. Hemberg and Bergdahl (2020), for example, have applied the theory of caritative caring with a person‐centred approach in palliative care.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…This fundamental focus on alleviating (or avoiding unnecessary) suffering is on an ontological level, thus applicable to various models of nursing and nursing care. Hemberg and Bergdahl (2020), for example, have applied the theory of caritative caring with a person‐centred approach in palliative care.…”
Section: Implications For Nursingmentioning
confidence: 99%
“…4 In order to be caring and compassionate, Newham et al 4 have found that it is necessary to see other persons as they truly are, which resonates with the ideas of nurses being morally perceptive and sensitive to patients. [8][9][10] Gallagher 11 stresses that it is admirable if health professionals are able to find opportunities to demonstrate kindness and compassion even in busy care contexts.…”
Section: Introductionmentioning
confidence: 99%
“…49 Time has been found to play a particularly important role in co-creation. 49,63 Many patients wish to receive comprehensive information about their health status, but as patients come closer to the end of life, this may decrease. 69,70 Research shows that existential issues are more profoundly present in end-of-life and palliative care than in any other care context.…”
Section: Introductionmentioning
confidence: 99%
“…60 In nursing, the concept of co-creation is defined as deep nursing: a solicitous and considerate co-created nursing process that entails a personal nursing practice enabled through perceptiveness and attention to patients, spending time with patients, and reflecting on nursing encounters. 49,[61][62][63] According to Palumbo, 64 co-creation relates to that patients should be involved in honest and comfortable relationships with their healthcare providers because patients are effective members of the healthcare team. Co-creation in nursing care is more than simple collaboration with patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation